OSTEOMYELITIS KRONIS MANDIBULA PASCA EKSTRAKSI GIGI DISERTAI BELL’S PALSY - Yayun Siti Rochmah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Chronic osteomyelitis mandibula is one of the complications from dental extraction. Inadequate wound handling can have an impact on the spread of infection in the surrounding tissue like nerve which results in facial nerve paralysis. The purpose is to present a rare case that facilitative nerve paralysis as a result of the spread of osteomyelitis infectionCase Management: A 69 years old woman with chief complains numbness onher lips accompanied by pus out beside the lower teeth. No sistemic disease. Panoramic radiograph showed abnormal bone-like sequester. Extraoral examination appeared the bluish color on the right cheek and there was right facial muscle paralysis. Debridement, sequesterectomy by general anesthesia and medication using ceftriaxone intravenous, ketorolac injection, multivitamin, and corticosteroid, physiotherapy for facial nerve paralyze, also.Discussion: Pathogenesis mandibular osteomyelitis involves contiguous spreadfrom an odontogenic focus infection. The bacteria produce an exotoxin, which, while unable to cross the blood-brain barrier, can have deleterious effects on thePeripheral Nerve System (Fasialis Nerve) in up to 75% of cases, with the severity of presentation correlating with the severity of the infection.Conclusion: Chronic mandibular osteomyelitis can spread the infection to around another anatomy oral cavity like facials nerves.